P16.01.A Factors predicting cognitive impairment after intrathecal methotrexate treatment in patients with non-small cell lung cancer and leptomeningeal disease. (5th September 2022) - Vilariño, N; Esparragosa, I; Marín, J; Alemany, M; Velasco, R; Jové, M; Brenes, J; Palmero, R; Brao, I; Arellano, M; Sala, R; Bruna, J; et al.
Abstract: Background: Leptomeningeal disease (LD) is a devastating cancer-related neurological complication. LD accounts for 4-15% of patients with non-small cell lung cancer (NSCLC). In this population, the median overall survival (OS) with intrathecal (IT) methotrexate (MTX) plus systemic therapy (ST) is 4-6 months (m). Until now, disease and treatment-related cognitive impairment (CI) has been poorly studied in this group. Material and Methods: Patients with NSCLC and LD treated with IT MTX in our institution between 2010 and 2021 were retrospectively studied. LD was diagnosed based on positive cerebrospinal fluid cytology or radiological findings in the brain/spinal MRI plus suitable clinical signs/symptoms. IT MTX (12mg twice weekly for 4 weeks, then 12mg weekly for 4 weeks) was given in combination with ST. Patients' clinical characteristics and patient-reported CI were assessed at baseline and at 3-months post IT MTX. A Kaplan-Meier survival analysis was performed. Primary endpoint: predictive factors of CI at 3m post IT MTX. Secondary endpoint: prognostic factors. Results: Out of 55 patients included, 51% were male and median age at LD diagnosis was 59 years old (range 38-78). Most patients had an ECOG PS≤1 (76.4%) and adenocarcinoma histology (83.6%). 47% of patients harbored EGFR mutation. In 23.6% of patients LD was diagnosed synchronously with lung tumor and for patients without LD at tumor diagnosis, the median time to LD development was 8m (range 0-73). Clinical features at LD diagnosis were 43.7% infratentorial symptoms, 29% CI, 20% multiple symptoms and 7% asymptomatic. At LD diagnosis, 53% of patients had synchronous brain metastases (BM) and in 38% the systemic disease was not controlled. 85.5% of patients received ST concurrently with IT MTX (N=22 chemotherapy, N=22 TKIs and N=3 immunotherapy). 14.5% of patients did not receive ST. Median OS from IT was 5m (95% CI 1.3-8.6). ECOG PS and ST administered concurrently with IT MTX was associated with longer OS (p<0.05). 23.6% of patients developed CI at 3m post IT therapy. Median OS for patients without and with CI post IT therapy was 6m (95% CI 0.7-11.3) vs 4m (95% CI 0.5-75) respectively (p=0.15). Patients with leukoencephalopathy at baseline (score≥2in the periventricular Fazekas' score) (p=0.033), women (p<0.01) and those ≥60 years (p=0.04) were more likely to present CI 3m post IT MTX. The presence of cardiovascular risk factors, previous brain radiotherapy and concurrent BM was not statistically associated with CI. Conclusion: In this cohort, 24% of patients with NSCLC and LD treated with IT MTX will develop CI 3m post treatment. Baseline leukoencephalopathy, female gender, elder than 60 years old were more likely to exhibit CI after IT MTX. A better characterization of these patients is warranted to develop new treatment strategies to prevent/reduce CI.